Analisis Kemampuan Guru Pendidikan Agama Islam Dalam Pelaksanaan Soal Penilaian Keterampilan Di SD Negeri Yogyakarta - Miqdad Tattaq Noto Sabdo; Anisah Indriati (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Analysis of the Ability of Islamic Religious Education Teachers in the Implementation of Skills Assessment Questions in Public Elementary YogyakartaThe implementation of skills assessment in the learning process in schools has various obstacles, one of which is the aspect of the teacher's ability as the implementing subject. These implementation .constraints need to be evaluated so that they can be improved in the future, thus this study will analyze the ability of Islamic Religious Education teachers in implementing skills assessment questions at Elementery Tegalyoso Gamping Sleman Yogyakarta. This study was designed with a descriptive qualitative approach used to make the discussion more relevant and in-depth, while the research data collection techniques were in the form of observation, interviews and documentation. The results of the study indicate that the implementation of skills assessment questions includes the stages of planning, implementing, and reporting performance. The acquisition of research data on teachers of Islamic Religious Education lessons at the three stages, shows that the teachers have carried out the stages according to the skill assessment design with value 94%, so that they can be categorized as